Role of GeneXpert in Rapid Molecular Detection of Extrapulmonary Tuberculosis in Tertiary Care Hospital - Kala Yadhav M L; Veena M (International Journal of Medical Research and Review, 2018)
Introduction: Tuberculosis, the most common infectious disease with prevalence of 9.6 million globally. Most prevalent (23%) in India. Extrapulmonary tuberculosis (EPTB) accounts for 20% of total burden of tuberculosis. Rapid detection of Mycobacterium Tuberculosis (MTB) is essential for effective disease management. CBNAAT (Cartridge Based NucleicAcid Amplification Test) or GeneXpert MTB/RIF assay - novel diagnostic tool to detect MTB and RIF resistance simultaneously. WHO recommends its utility for non-respiratory samples also. Burden of EPTB and drug resistance vary from place to place.Objective: Study was conducted to gather information about burden of disease in our locality and to assesutility of CBNAAT in detecting MTB and rifampicin resistance in suspected EPTB cases.Methods: Retrospective analysis of 281 samples from suspected cases collected in falcon tubes and processed using CBNAAT.Result: Total of 281 extrapulmonary samples received, 67(23.8%) were positive and 214(76.1%) were negative for MTB. Of 67 positives, RIF resistance detected in 1(1.49%) case. Maximum number of MTB detected in the age group 21-30 years (n=23, 34.3%). Among 165 males and 116 females, MTB detected in 44(26.6%) and 23(19.8%) respectively. Out of 281 patients, 24(8.54%) were HIV positive. Of these 24, only 8(33.3%) found positive for MTB. Among 257 non-HIV patients, MTB detected in 59(22.9%). Among different samples received, maximum number were Pleural fluid n=115(40.9%) and Maximum MTB positives found in FNAC (of lymphnodes) samples [n=35(52.2%)].: CBNAAT is a rapid test to detect MTB and rifampicin resistance simultaneously in EPTB and it reduced the treatment abuse in suspected cases.